2017
DOI: 10.1039/c6dt03097a
|View full text |Cite
|
Sign up to set email alerts
|

An immobilized symmetrical bis-(NHC) palladium complex as a highly efficient and recyclable Suzuki–Miyaura catalyst in aerobic aqueous media

Abstract: A bis-N-heterocyclic carbene (NHC) functionalized with chloropropyltriethoxysilane over silica was used to synthesize a well-defined immobilized palladium complex. This complex is a suitable and easily retrievable catalyst for Suzuki-Miyaura cross-coupling reactions under mild aqueous conditions. Excellent yields and conversions were obtained with low palladium loadings (down to 0.03 mol% Pd). The catalyst can be reused up to six cycles without the loss of its activity. The catalytic role of the NHC complex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…The biphenyl homocoupled product obtained was in a trace amount, which indicated that the SB‐Pd@MNPs nanomagnetic catalyst is highly selective . A plausible mechanism for our newly investigated SB‐Pd@MNPs nanomagnetic catalyst is illustrated in Scheme which delivers the C‐C coupling products via possible mechanistic intermediates ( I – III ) …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The biphenyl homocoupled product obtained was in a trace amount, which indicated that the SB‐Pd@MNPs nanomagnetic catalyst is highly selective . A plausible mechanism for our newly investigated SB‐Pd@MNPs nanomagnetic catalyst is illustrated in Scheme which delivers the C‐C coupling products via possible mechanistic intermediates ( I – III ) …”
Section: Resultsmentioning
confidence: 86%
“…The Suzuki–Miyaura cross‐coupling reactions are some of the most extensively used C‐C bond forming reactions in synthetic chemistry and have been utilized as an efficient method to obtain pharmaceutical drugs, complex natural products, engineering materials such as liquid crystals, molecular wires and conducting polymers . Numerous catalysts have been developed for Suzuki–Miyaura cross‐coupling reactions . Among these, Schiff base–transition metal complexes have exhibited superior catalytic activities and several homogeneous catalysts have been developed .…”
Section: Introductionmentioning
confidence: 99%
“…The generally accepted mechanisms for Pd‐catalyzed Suzuki–Miyaura and Mizoroki–Heck reactions are shown in Scheme . Both the mechanisms start with oxidative addition of the organohalide (R 1 ‐X) to the Pd (0) to form a Pd (II) complex …”
Section: Resultsmentioning
confidence: 99%
“…As can be seen, MNP@SiO 2 -SBA exhibits a typical type-IV curve with an H2 hysteresis loop. [47,48] Appearance and increase in intensity of Pd 3d doublet corresponding to Pd(0) were observed from XPS measurements followed by a decrease in Pd(II) doublet intensity. The obtained results indicate that MNPs do not block the intrachannel space, allowing molecules to enter the channels for subsequent modifications.…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 95%